A commentary on the ninth and tenth books of the Aithiopica of Heliodoros - Morgan, J (1978)
This commentary attempts to combine the functions of a traditional textual and linguistic study with those of literary criticism. It deals with the many passages in the last two books of the Aithiopica where the text is in doubt or its meaning obscure, and discusses a variety of stylistic points, presenting parallels for many of Heliodoros' peculiar usages. It adduces comparative material to relate Heliodoros' geographical, anthropological and historical setting both to reality and to the beliefs and practices of the ancient world. It also offers the reader of Heliodoros a running commentary on larger issues of narrative technique, characterisation, structure and overall interpretation, shoving how Bks.9 & 10 form the climax of the novel; these elements together form a judgement on Heliodoros' stature as a writer and his success as a novelist. The Introduction offers a connected treatment of four important themes: Section 1 discusses the dating of the Aithiopica and argues that it must have been written after Shapur's siege of Nisibis in AD 350, but that Heliodoros was not drawing on Julian's account of the siege; the possibility of a shared source is suggested; Section 2 discusses the religious background of the novel and rejects the religious interpretation, arguing that the many references to the supernatural do not shew a consistent view of divine intervention in human affairs and derive from a purely literary desire for unity and forward movement; Section 3 analyses Heliodoros' attempt to achieve realism and classifies the devices he uses; Section 4 discusses the author's prose style and isolates some characteristic features.